2020
DOI: 10.1002/for.2642
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting interest rates through Vasicek and CIR models: A partitioning approach

Abstract: The aim of this paper is to propose a new methodology that allows forecasting, through Vasicek and CIR models, of future expected interest rates (for each maturity) based on rolling windows from observed financial market data. The novelty, apart from the use of those models not for pricing but for forecasting the expected rates at a given maturity, consists in an appropriate partitioning of the data sample. This allows capturing all the statistically significant time changes in volatility of interest rates, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…As empirically investigated in Orlando and Bufalo, 3 returns, either standardized or not, do not seem to be unconditionally normally distributed. They often show a significant amount of skewness and extra‐kurtosis 4‐7 . Skew normal distributions were first introduced by Azzalini 8 and Henze 9 and have gained some momentum because of their suitability in modeling real data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As empirically investigated in Orlando and Bufalo, 3 returns, either standardized or not, do not seem to be unconditionally normally distributed. They often show a significant amount of skewness and extra‐kurtosis 4‐7 . Skew normal distributions were first introduced by Azzalini 8 and Henze 9 and have gained some momentum because of their suitability in modeling real data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of applications, parametric models and model‐free are the basis of the so‐called dynamic conditional score (DCS) 13 where the updating of the score function is determining a sort of partitioning of the dataset 14,15 . In fact, DCS models often employ t‐skew distributions and they have been used for a variety of applications: value at risk (VaR) and expected shortfall (ES), 16 FX, 17 mortgage defaults, 18 and so forth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the market needs a model that is able to cope with changing regimes, shocks, and negative rates. To this end, we have proposed within the CIR framework Orlando et al (2018Orlando et al ( , 2019aOrlando et al ( , 2019bOrlando et al ( , 2020 a new methodology that fits well the structure of interest rates and preserves the analytical tractability of the original CIR model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from turning a short-rate model used for pricing into a forecasting tool, the novelty of the CIR# consists in an appropriate partitioning of the dataset into subgroups. To this end, in Orlando et al (2020), it was shown how the said partitioning enables us to capture statistically significant time changes in volatility of interest rates. This, in turn, implies modeling sudden changes/jumps in data.…”
Section: Introductionmentioning
confidence: 99%
“…Orlando et al suggest in several papers (cf. [22][23][24]) a new framework, which they call CIR# model, that fits the term structure of interest rates. Additionally, it preserves the market volatility, as well as the analytical tractability of the original CIR model.…”
Section: Review Of the Literature And Comparisonmentioning
confidence: 99%